2010
DOI: 10.1063/1.3422340
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Calculations for a 30 Hz, 4 K Regenerator With Helium-3 Working Fluid

Abstract: The NIST numerical software, REGEN3.3, which incorporates both He-4 and He-3 properties, was used to calculate the losses and second law efficiencies of 4 K regenerators operating at 30 Hz. Operating parameters, such as average pressure, pressure ratio, and warm-end temperature were varied to investigate the effect of non-ideal gas properties. Regenerator parameters such as matrix material and shape, hydraulic diameter, and regenerator geometry were varied to investigate losses due to non-ideal regenerator beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Operating at higher frequency ranges, 30 Hz to 60 Hz, leads to greater regenerator losses at 4 K when not operating at ideal conditions. 2 The optimization between the phase angle of the pressure and the flow, where flow lags pressure, is critical at the cold-end of a 4 K cryocooler to provide optimum efficiency. Recent modeling has shown that the optimum phase required at the cold-end is 30°, which would require a 60° phase difference at the pulse tube warm-end.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…Operating at higher frequency ranges, 30 Hz to 60 Hz, leads to greater regenerator losses at 4 K when not operating at ideal conditions. 2 The optimization between the phase angle of the pressure and the flow, where flow lags pressure, is critical at the cold-end of a 4 K cryocooler to provide optimum efficiency. Recent modeling has shown that the optimum phase required at the cold-end is 30°, which would require a 60° phase difference at the pulse tube warm-end.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…Recently the use of 3 He in place of the 4 He in a 30 Hz pulse tube cryocooler has shown increased efficiency at 4 K [32]. Modeling studies [43] have shown that optimized regenerators using 3 He can have significantly improved performance, especially if the average pressure is reduced to about 0.5-1.0 MPa. Low-porosity matrix geometries in the high heat capacity materials can lead to further increases in the regenerator performance.…”
Section: High Efficiency Cryocoolers For 4 Kmentioning
confidence: 99%
“…In collaboration with our group, Radebaugh et al [8,9] from NIST developed a new version of the regenerator modeling code-REGEN3.3, which incorporates the thermophysical properties of both 4 He and 3 He. Preliminary calculations of high frequency cryocoolers with 3 He and 4 He have been conducted to investigate how geometry and materials, among other aspects, affect the performance of the regenerator working at 4 K at the cold end and 20 K at the hot end.…”
mentioning
confidence: 99%